Seesaw signal processing in pineal cells: homologous sensitization of adrenergic stimulation of cyclic GMP accompanies homologous desensitization of beta-adrenergic stimulation of cyclic AMP. - Klein, D C (1981)
Studies of the adrenergic regulation of cyclic GMP in the pineal gland show that (-)-norepinephrine stimulates cyclic GMP primarily in pineal cells, rather than in nerve endings as previously thought. The response exhibits the interesting and unusual characteristic of homologous sensitization: It is maintained by neural stimulation and disappears gradually as a consequence of depressed neural stimulation, due to denervation or decentralization of the superior cervical ganglia or to constant light. The response is restored in intact animals that had been in a constant-light environment when they are returned to a normal light cycle and in ganglionectomized animals by norepinephrine treatment. These findings are especially interesting because the pineal adrenergic--cyclic AMP stimulus--response system exhibits homologous desensitization. The occurrence of homologous sensitization of a cyclic GMP response and desensitization of a cyclic AMP response, which we term seesaw signal processing, in the same tissue or cell has intriguing implications. It provides a mechanism through which the qualitative nature of a multicomponent response can be modified. Such a mechanism could play a role in signal processing by neural or neuroendocrine tissues that release two or more extracellular messages.